Young Children's Interpretation of Multidigit Number Names: From Emerging Competence to Mastery. Issue 3 (6th December 2013) - Mix, Kelly S.; Prather, Richard W.; Smith, Linda B.; Stockton, Jerri DaSha
<x xml:space="preserve">Abstract</x> This study assessed whether a sample of two hundred seven 3‐ to 7‐year‐olds could interpret multidigit numerals using simple identification and comparison tasks. Contrary to the view that young children do not understand place value, even 3‐year‐olds demonstrated some competence on these tasks. Ceiling was reached by first grade. When training was provided, there were significant gains, suggesting that children can improve their partial understandings with input. Findings add to what is known about the processes of symbolic development and the incidental learning that occurs prior to schooling, as well as specifying more precisely what place value misconceptions remain as children enter the educational system.